2019
DOI: 10.1186/s12889-019-6494-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ART scale-up and female migration intensity on risk of HIV acquisition: results from a population-based cohort in KwaZulu-Natal, South Africa

Abstract: Background Despite increased antiretroviral therapy (ART) coverage, the incidence of HIV infection among women in rural South Africa remains high. While many socio-demographic and behavioral factors have been identified, the effect of female migration intensity on the risk of HIV acquisition before and after ART scale-up has not been evaluated in the country. Methods We followed 13,315 female participants aged 15–49 who were HIV-uninfected at baseline and recorded their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…We report that more cumulative time spent outside the study area increased both the male and female risk of HIV acquisition, a result that is supported by previous research [ 12 , 16 , 19 , 20 , 29 ]. For example, one of these studies showed that the HIV acquisition risk increased by 50% when men spent 44% and women 90% of their time away from their household residence [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…We report that more cumulative time spent outside the study area increased both the male and female risk of HIV acquisition, a result that is supported by previous research [ 12 , 16 , 19 , 20 , 29 ]. For example, one of these studies showed that the HIV acquisition risk increased by 50% when men spent 44% and women 90% of their time away from their household residence [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…To address potential sources of confounding, we obtained adjusted IRRs using Poisson regression models. Based on previous research undertaken in the AHRI study area, we included age 33 , condom use 38 , marital status 39 , male circumcision status 39 , household socio-economic status (in tertiles) 40 , cumulative time spent outside the study area 37,41 , and the HIV prevalence of the participant’s surrounding community 29 . We ran the analyses separately for men and women, with opposite-sex ART coverage and opposite-sex HIV prevalence covariates, and excluded male circumcision status from the female-only models.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review by Weine, et al showed that prolonged or frequent absences were among the most frequently cited determinants of HIV risk in studies involving labor migrants [ 30 ]. Indeed, length of time spent away from home has been shown to be a strong predictor of HIV positive status in several international settings [ 31 33 ]. A previous study based on large surveys of male migrants in the Russian Federation has found that difficulty in accessing healthcare services and limited health education contributed to Tajik migrants’ HIV vulnerability [ 17 ].…”
Section: Discussionmentioning
confidence: 99%